The Impact of Viral Load and Time to Onset of Cytomegalovirus Replication on Long-Term Graft Survival after Kidney Transplantation. Issue 6 (August 2017) - Reischig, Tomas; Kacer, Martin; Hruba, Petra; Jindra, Pavel; Hes, Ondrej; Lysak, Daniel; Bouda, Mirko; Viklicky, Ondrej
Background: Asymptomatic cytomegalovirus (CMV) infection is associated with graft dysfunction and failure. However, no study assessed CMV viral load in terms of the risk for graft failure. Methods: In a prospective cohort of kidney transplant recipients, we assessed the impact of CMV DNAemia on the overall graft survival and the incidence of moderate-to-severe interstitial fibrosis and tubular atrophy (IF/TA) in protocol biopsy at 36 months. CMV DNAemia was stratified by viral load in whole blood. Results: A total of 180 patients transplanted from October 2003 through January 2011 were included and followed for 4 years; 87 (48%) patients received 3-month prophylaxis with valacyclovir and 45 (25%) with valganciclovir; 48 (27%) were managed by pre-emptive therapy. Within 12 months of transplantation, CMV DNAemia developed in 102 (57%) patients with 36 (20%) having a viral load of ≥2, 000 copies/ml. Multivariate Cox analysis identified CMV DNAemia as an independent risk factor for graft loss (hazard ratio 3.42; P =0.020); however, after stratification by viral load, only CMV DNAemia ≥2, 000 copies/ml (hazard ratio 7.62; P <0.001) remained significant. Both early-onset (<3 months; P =0.048) and late-onset (>3 months; P <0.001) CMV DNAemia ≥2, 000 copies/ml were risk factors for graft loss. The incidence of moderate-to-severe IF/TA was not significantly influenced by CMV DNAemia. Conclusions: Kidney transplant recipients having CMV DNAemia with a higher viral load irrespective of the time to onset are at increased risk for graft loss.